Examination of wastewater generated in wood drying kilns - Muhammed Enes Tepedelen; Uğur Özkan; Halil Turgut Şahin (Turkish Journal of Forestry)
In this study, the physical treatment of wastewater obtained during the kiln drying of Calabrian pine (Pinus brutia Ten.) wood in a timber processing plant in Isparta was investigated by centrifugation technique. The wastewater samples were centrifuged at 1000 rpm (constant speed) for 2 to 10 minutes of duration, and some selected wastewater evaluation parameters such as pH, electrical conductivity (EC), total dissolved solids (TDS), suspended solids (SS), dissolved oxygen (DO), and turbidity (NTU) were analyzed. Also, the data obtained were statistically analyzed at 95% confidence level. When significant differences were identified, Duncan's multiple range test was applied to evaluate the homogeneity of mean values across the groups. The results showed that centrifugation caused a significant reduction in turbidity and suspended solids. It was calculated for the turbidity, decreased from 31.49 NTU to 14.60 NTU, and the suspended solids content decreased by 71%, from 38 mg/L to 11 mg/L. However, no significant change was observed in pH, EC, and TDS values. Additionally, the color analysis of the water revealed that centrifugation had a measurable effect on the total color difference (ΔE). This study concludes that while centrifugation is effective in reducing physical pollution of waste waters, it causes not noticeable changes in the chemical composition, providing useful data for future similar wastewater treatment research.